STRATEGI PENGEMBANGAN KULINER BERBAHAN DASAR KOPI DI DESA WISATA SIRNA JAYA KECAMATAN SUKAMAKMUR, KABUPATEN BOGOR - Rahmat, Timotius Agus; Basalamah, Anwar; Bahri, Asep Syaiful; Susanto, Shandy; Chelsea Lim; Genoviene, Feliska; Riyanto, Budi (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This study aims to formulate a strategy for developing coffee-based culinary products to enhance economic value and strengthen the identity of Sirna Jaya Tourism Village, Sukamakmur District, Bogor Regency. A qualitative case study approach was employed, supported by SWOT and Analytic Hierarchy Process (AHP) analyses. Data were collected through field observations, in-depth interviews, Focus Group Discussions (FGDs), and literature studies. The findings reveal that coffee-based culinary products hold strong development potential, with priority given to coffee-based food, ready-to-drink bottled coffee (RTD), and coffee ice cream. The dominant strategic factor was market potential (0.45), followed by tourism attractiveness (0.25), production cost (0.18), and technological feasibility (0.12). Recommended strategies include diversifying coffee-based culinary products, enhancing community capacity through training, and strengthening the village’s digital branding. The study highlights the importance of integrating culinary innovation, agrotourism, and the creative economy to foster sustainable, community-based tourism (CBT).